The Petrology and Geochemistry of the 2021 Fagradalsfjall Eruption, Iceland: An Eruption Sourced From Multiple, Compositionally Diverse, Near‐Moho Sills - E. W. Marshall; A. Caracciolo; E. Bali; S. A. Halldórsson; S. Matthews; E. Ranta; M. B. Rasmussen; J. G. Robin; G. H. Guðfinnson; J. Maclennan; C. Bosq; D. Auclair; et al. (AGU Advances)
Abstract Magmatic processes at the crust‐mantle boundary (i.e., Moho) are commonly studied post facto at fossil ophiolites, oceanic core complexes, or inferred from the compositions of crystals or melt inclusions. The 2021 eruption at Fagradalsfjall on the Reykjanes Peninsula, Iceland, was supplied from magma bodies near the Moho and offers a unique opportunity to study the timescales, structure, and syn‐eruptive processes of near‐Moho magmatic systems at ∼15 km depth. Here, we present a comprehensive petrological and geochemical investigation of the full 183 day eruption that is based on frequent sampling of the eruption. Lavas erupted in the first 45 days displayed significant and sudden changes in geochemistry, followed by lower amplitude fluctuations until the end of the eruption. This variability can be explained by contribution from multiple magma bodies, as best distinguished using Sr‐Nd‐Hf‐Pb isotope systematics. The lavas display unusual trace element and radiogenic isotope compositions compared to other Icelandic basalts, but are similar to other rare, highly incompatible element enriched lavas on the Reykjanes Peninsula, and thus these lavas may represent a distinct suite of Reykjanes Peninsula basalts. Our geochemical and petrological observations show that numerous, compositionally variable bodies of magma must exist in the lowermost crust or at the crust‐mantle boundary. These near‐Moho magma bodies transfer magma between one another on timescales as short as days‐to‐months, but partially crystallize over longer time periods, and periodically inject into the overlying crust.